The benefit of the visual aspect of the graphic novel in development of learning process - ABBAS, WALEED ATTWAN (International Journal of Psychosocial Rehabilitation, 2020)
The paper focuses on the development of the graphic novel from a juvenile medium to a serious means of teaching in order to overcome the difficulties of teaching literary texts in classroom. It also sheds light on the various devices of graphic novels as adaptable key aspects of the genre to classroom teaching and as innovative and motivating teaching material. This research study proved the practicality of using a graphic novel to teach classical literature. The paper has also delineated the opportunities such innovative teaching method would offer to students compared to a narrative literary genre through a teaching class experience.